Local taxes as a source of revenue of the local self-government. Analysis of a property tax, an agricultural and forest tax on the example of gmina Lidzbark in 2010–2015 - Daria Zaborek; Krzysztof Czarnecki (Prawo Budżetowe Państwa i Samorządu)
According to Art. 167 of Polish Constitution, there are three main sources of local self-governments revenues: an own income, subsidies and grants. The own income of local communes (gminy) consists of local taxes and fees, including taxes which may also be collectively called “land taxes”. Those taxes include a property tax, an agricultural tax and a forest tax. The authorities of local self-governments are entitled to decide on some aspects of local taxes, especially they are able to establish tax rates. The article presents land taxes as a source of revenue of gmina Lidzbark in the years 2010–2015.